MiR-335-3p/miR-155-5p Involved in IGFBP7-AS1–Enhanced Odontogenic Differentiation - Ningxin Zhu; Dan Wang; Fei Xie; Man Qin; Yuanyuan Wang (International Dental Journal, 2023)
Background: The differentiation of stem cells from exfoliated deciduous teeth (SHEDs) into odontoblasts determines the regeneration of dentin-pulp complex. Non-coding RNAs (ncRNAs), including microRNA (miRNA) and long non-coding RNA (lncRNA), participate in many multiple biological processes, but the specific miRNAs involved in odontogenesis are incompletely defined. It was confirmed that lncRNA IGFBP7-AS1 could positively regulate odontogenetic differentiation in SHEDs. To investigate the downstream mechanisms of this process, miR-335-3p and miR-155-5p were found to be closely related with SHED odontogenic differentiation through whole-genome sequencing. The aim of the current study was to determine the role of miR-335-3p/miR-155-5p in IGFBP7-AS1–enhanced SHED differentiation and explore the potential mechanism of IGFBP7-AS1–mediated odontogenesis. Methods: Putative miR-335-3p/miR-155-5p binding sites within IGFBP7-AS1 were identified by bioinformatics analysis, and the binding of miR-335-3p/miR-155-5p to these sites was confirmed by dual-luciferase reporter gene assays. The effects of miR-335-3p/miR-155-5p in odontogenesis were detected by tissue nonspecific alkaline phosphatase staining, Alizarin red staining, quantitative real-time polymerase chain reaction (qRT-PCR) analyses, and western blot testing. The molecular mechanisms of miR-335-3p/miR-155-5p involved in IGFBP7-AS1–mediated odontogenesis were analysed by qRT-PCR and western blot testing. Results: Dual-luciferase reporter gene assays showed that miR-335-3p/miR-155-5p could directly bind to IGFBP7-AS1. MiR-335-3p and miR-155-5p both could down-regulate dentin sialophosphoprotein expression, and both miRNAs could inhibit IGFBP7-AS1–mediated SHED odontogenetic differentiation via suppression of the extracellular signal-regulated kinase (ERK) pathway. Conclusions: Both miR-335-3p and miR-155-5p were negative regulators to IGFBP7-AS1-enhanced odontogenic differentiation of SHED through suppression of the ERK pathway.